The dual specificity phosphatase 2 gene is hypermethylated in human cancer and regulated by epigenetic mechanisms - Haag, Tanja (BMC Cancer, 2016)
BACKGROUND: Dual specificity phosphatases are a class of tumor-associated proteins involved in the negative regulation of the MAP kinase pathway. Downregulation of the dual specificity phosphatase 2 (DUSP2) has been reported in cancer. Epigenetic silencing of tumor suppressor genes by abnormal promoter methylation is a frequent mechanism in oncogenesis. It has been shown that the epigenetic factor CTCF is involved in the regulation of tumor suppressor genes. METHODS: We analyzed the promoter hypermethylation of DUSP2 in human cancer, including primary Merkel cell carcinoma by bisulfite restriction analysis and pyrosequencing. Moreover we analyzed the impact of a DNA methyltransferase inhibitor (5-Aza-dC) and CTCF on the epigenetic regulation of DUSP2 by qRT-PCR, promoter assay, chromatin immuno-precipitation and methylation analysis. RESULTS: Here we report a significant tumor-specific hypermethylation of DUSP2 in primary Merkel cell carcinoma (p = 0.05). An increase in methylation of DUSP2 was also found in 17 out of 24 (71 %) cancer cell lines, including skin and lung cancer. Treatment of cancer cells with 5-Aza-dC induced DUSP2 expression by its promoter demethylation, Additionally we observed that CTCF induces DUSP2 expression in cell lines that exhibit silencing of DUSP2. This reactivation was accompanied by increased CTCF binding and demethylation of the DUSP2 promoter. CONCLUSIONS: Our data show that aberrant epigenetic inactivation of DUSP2 occurs in carcinogenesis and that CTCF is involved in the epigenetic regulation of DUSP2 expression. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12885-016-2087-6) contains supplementary material, which is available to authorized users.